2022
DOI: 10.1111/hex.13644
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based health literacy focused intervention for cervical cancer control among Black women living with human immunodeficiency virus: A randomized pilot trial

Abstract: Background Health literacy plays an essential role in how individuals process health information to make decisions about health behaviours including cancer screening. Research is scarce to address health literacy as a strategy to improve cancer screening participation among women living with human immunodeficiency virus (HIV), particularly Black women who, despite the heavy burden of cervical cancer, report consistently low screening rates. Aim To assess the feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…CNN offers different layers, such as convolutional layers, which are the most important and relevant. Convolutional layers are a set of filters that wrap around an input, resulting in feature maps being produced as output as in Equation (7). CNN uses the image and applies filters to it while extracting deep features that represent the image [43].…”
Section: Cnn For Deep-feature Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…CNN offers different layers, such as convolutional layers, which are the most important and relevant. Convolutional layers are a set of filters that wrap around an input, resulting in feature maps being produced as output as in Equation (7). CNN uses the image and applies filters to it while extracting deep features that represent the image [43].…”
Section: Cnn For Deep-feature Extractionmentioning
confidence: 99%
“…The classification layers were removed from the models, and the convolutional, pooling, and auxiliary layers were preserved. ResNet50, VGG19, and GoogLeNet models generated high-level feature maps as follows: (3, 3, 512), (7,7,512), and (7, 7, 512), respectively. The high-level feature maps were converted into single-feature vectors for each image by the global average pooling (GAP) layer and saved in feature vectors of size 2048, 4096, and 4096 for ResNet50, VGG19, and GoogLeNet, respectively.…”
Section: Cnn For Deep-feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…women in the control group. (50% vs. 21.9%, p =0.025) (Han et al, 2023) Another health literacy-focused intervention cluster randomized trial among Korean American women reported higher odds of undergoing a mammogram (18.5 times; 95% confidence interval [CI] = 9.2, 37.4) and Papanicolaou test (13.3 times; 95% CI = 7.9, 22.3) in the intervention group compared to the control group, thus successfully promoting cancer-screening behavior. (Han et al, 2017) There is a dearth of HL research on cancer screening in India, which often uses proxy variables like disease knowledge and attitude, as well as socio-demographic correlates like education, socioeconomic status, and rurality (Changkun et al, 2022).…”
mentioning
confidence: 93%